Efektivitas Extraoral Suction dalam Praktik Kedokteran Gigi di Masa Pandemi COVID-19 - Carolina Stevanie (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
COVID-19 virus can be potentially transmitted by aerosol. Aerosol is defined as small particles of less than 0.5-10 micron which can be produced during talking, coughing and sneezing. In addition, aerosol can be produced by instrumentation during dental procedure. The purpose of this literature review is to explain the effectiveness of extra-oral suction usage for reducing aerosol production and circulation during dental procedure. COVID-19 virus brought by aerosol tend to stay airborne for 3 hours with 1.1-1.2 hours of lifespan. By using aerosol as transport media, virus can travel almost 200.000 km horizontally. A combination of intra- and extra-oral suction in dental clinics or hospitals are believed to be effective for reducing the risk of COVID-19 transmission by aerosol during dental practice. The study recommends further research by microbiology specialists and dental technology experts to confirm this.